2016
DOI: 10.1080/00222895.2016.1204262
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Responses in Young and Older Adults Following a Perturbation to the Support Surface During Gait

Abstract: The objective of this work was to investigate the influence perturbation direction has on postural responses during overground gait, and whether these responses are age related. Differences in stepping patterns following perturbations of the support surface were examined in the frontal and sagittal planes during forward walking. Eleven young and 10 older adults completed Mini BESTest, hip strength tests, and 45 perturbed walking trials, triggered on heel contact. Lateral perturbations were more challenging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…In contrast to our expectations based on previous studies [ 6 , 7 , 44 , 47 ], we did not find any differences in perturbation effects and recovery responses between young and older adults. This may be explained by the fact that most of our older adults were recruited through fitness classes and therefore very fit and healthy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our expectations based on previous studies [ 6 , 7 , 44 , 47 ], we did not find any differences in perturbation effects and recovery responses between young and older adults. This may be explained by the fact that most of our older adults were recruited through fitness classes and therefore very fit and healthy.…”
Section: Discussioncontrasting
confidence: 99%
“…Successful recovery from a perturbation is determined by the combination of stability prior and in response to the perturbation. By proactively increasing gait stability, one might reduce the effect of the perturbation and minimize risk of falling [ 44 46 ]. Although we did not aim to evaluate such adaptations, the data revealed that participants proactively adapted their gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect concerns the differences between-age groups in the spatial characteristics of the first step. The shorter and lower step showed by older participants following the perturbation is in line with findings from previous studies focusing on reactive stepping following mediolateral perturbations during standing and walking in place (Maki et al 2000a, b), steady-state walking (McIntosh et al 2017) and gait initiation (Shulman et al 2018). As also suggested in these studies, these changes in step characteristics may reflect the need for a more cautious stepping strategy to reduce the risk of losing balance and falling .…”
Section: Biomechanical Adjustments Relevant To Increase First-step Stsupporting
confidence: 90%
“…Perturbations in one direction often elicit responses perpendicular to the perturbation direction (Madehkhaksar et al 2018; Martelli et al 2016; O’Connor and Kuo 2009; Vlutters et al 2018) as responses between the sagittal and frontal planes are dynamically coupled (Bauby and Kuo 2000; Buurke et al 2020). Medial-lateral perturbations are often more challenging than the anterior-posterior perturbations (Madehkhaksar et al 2018; McIntosh et al 2017) because medial-lateral balance requires active control during walking (Rankin et al 2014; Reimold et al 2020). In our study, medial-lateral perturbations were not more challenging than the anterior-posterior perturbations, which could be related to the magnitude of the shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations during walking can induce potential losses of balance and elicit corrective locomotor adaptations, which are useful for understanding human balance control (Mansfield et al 2015; Torres-Oviedo et al 2011). There are multiple approaches to perturb gait stability, including split-belt walking (Buurke et al 2018; Torres-Oviedo et al 2011), visual flow distortions (Franz et al 2016; O’Connor and Kuo 2009), waist pulling (Hof et al 2010; Vlutters et al 2018), platform displacements (Afschrift et al 2018; McIntosh et al 2017), and rapid changes in treadmill belt speed (Debelle et al 2020; Patel and Bhatt 2018). Studies using discrete perturbations such as waist pulling, platform displacements, and changes in treadmill belt speeds often apply the perturbation once out of every 5-20 strides (Afschrift et al 2018; Debelle et al 2020; Hof et al 2010; McIntosh et al 2017; Patel and Bhatt 2018; Vlutters et al 2018).…”
Section: Introductionmentioning
confidence: 99%